Formulation, development and characterization of mucoadhesive film for treatment of vaginal candidiasis - Mishra, Renuka; Joshi, Priyanka; Mehta, Tejal (International Journal of Pharmaceutical Investigation)
Objective: The objective of the present investigation was formulation, optimization and characterization of mucoadhesive film of clotrimazole (CT) which is patient-convenient and provides an effective alternative for the treatment of vaginal candidiasis. CT is an antimycotic drug applied locally for the treatment of vaginal candidiasis. Materials and Methods: Mucoadhesive vaginal films were prepared by solvent casting technique using hydroxyl propylcellulose and sodium alginate as polymers. Propylene glycol and polyethylene glycol-400 were evaluated as plasticizers. The mucoadhesive vaginal films were evaluated for percentage elongation, tensile strength, folding endurance, drug content, in vitro disintegration time, in vitro dissolution study, swelling index, bioadhesive strength, and diffusion study. Results: Among various permeation enhancers used, isopropyl myristate was found to be suitable. To evaluate the role of the concentration of permeation enhancer and concentration of polymers in the optimization of mucoadhesive vaginal film, 32 full factorial design was employed. Optimized batch showed in vitro disintegration time, 18 min; drug content, 99.83%; and tensile strength, 502.1 g/mm2. In vitro diffusion study showed that 77% drug diffusion occurred in 6 h. This batch was further evaluated by scanning electron microscopy indicating uniformity of the film. In vitro Lactobacillus inhibition and in vitro antifungal activity of optimized batch showed an inhibitory effect against Candida albicans and no effect on Lactobacillus, which is a normal component of vaginal flora. Conclusion: Mucoadhesive vaginal film of CT is an effective dosage form for the treatment of vaginal candidiasis.
Keywords: Clotrimazole; hydroxypropyl cellulose; mucoadhesive film; sodium alginate; vaginal candidiasis